Production costs and competitiveness of potato in the state of Mexico. - Morales-Hernández, José Luis (2011)
The objective of this work was to determine costs and rentability of potato crop. The study was conducted from March to September 2009 at the stateof Mexico, base don the information obtained from surveyswith stratiﬁ ed sampling of large producers (more than 10ha), middle (5-10 ha) and small (1-5 ha) in ten localities.The methodology used was The Matrix of Analysis ofPolicy (MAP), whose main purpose is to measure the effectsof trade liberation and the efﬁ ciency of the productionsystems. The results show that large producers had higheryield (6.421 to 8.765 US$) than middle-size (5.170 to8.291 US$) and small producers (3.107 to 6.658 US$).Potato farming paid the market price of the internal factors,including a return to the capital. The relation of privatecosts, on average, was lower in large producers (0,24) thanin middle (0,25) and small producers (0,30), which indicateshigher yields and competitiveness of large producers. Theaverage consumption in the total income in large producerswas 25%, and in middle and small producers was 27% and33% respectively, which integrates the percentage of thepurchase of supplies. Complementarily, the added value inthe total income, for large producers, was on average 75%,and 73 and 67% for middle and small producers, whichshows the contribution of farming to job creation. Theproductive activity of potato farming in 2009 was proﬁ tableaccording to the balance of received and paid bills.